Piperazine derivatives as dangerous abused compounds - Welz Anna; Koba Marcin (Acta Pharmaceutica)
Piperazine derivatives are a group of compounds with a psychostimulant effect. They are an alternative to illegal drugs. They are being searched for recreational use due to their psychoactive and hallucinogenic effects. The high popularity of these compounds can be noticed all over the world due to easy purchase, lack of legal regulations and incorrect assessment of the safety of use. The recreational use of piperazine derivatives can often result in chronic and acute health problems and additionally with unpredictable remote effects. It is also common to take mixtures of psychoactive compounds. This hinders the correct diagnosis and treatment of patients with poisoning. The presented work is an illustration of the wide problem of piperazine derivatives abuse. The health effects and the possibility of identifying these compounds in preparations and biological material are described.